Shortcuts in German Grammar: A Percentage Approach Phase 1: Adjective endings - Partridge, John; Krauß, Susanne (Linguistik Online, 2012)
German grammar is constantly perceived as difficult, a strong disincentive to learning the language, yet the underlying principles are basically simple. If applied consistently, using uncomplicated techniques based on the concept of markedness, German of a high level of accuracy can be produced.Starting with the unjustifiably much-feared adjective endings, this pilot scheme, funded with the help of the Challenge Fund of the University of Kent, demonstrates the principles of German word-order and the marking of case and gender and how, with some minor adjustment, the easily learnable der/die/das paradigm and the awareness that once this has been mastered and case and gender have already been marked, only one of the two unmarked endings -e or -en is required to give all the necessary patterns for producing correctly inflected adjective endings. If case and gender are not marked by an article the endings of der/ die/ das can with some slight modifications be added to the adjective. So with this easily acquired knowledge, adjective endings can be handled with confidence.On this basis the program, still a work in progress, offers a theoretical grounding couched in understandable terms, a terminological glossary and an easily accessible expandable set of technologically based exercises with extensive linked help functions. These can be used serially as an entire learning unit or selectively to enable students to put their knowledge into practice and improve their skill and success in German.Following this pilot, the approach is to be extended to other common grammatical problems, e. g. word order, passive (Zustands- vs. Vorgangspassiv), indirect speech, subordinate clauses, prepositions of movement and location, past tense forms and subjunctive use.